The mathematics problem section of La Escuela bulletin (1913-1916) - Muñoz Escolano, José María; Oller Marcén, Antonio Miguel; Santágueda Villanueva, María (Historia y Memoria de la Educación, 2022)
The bulletin La Escuela. Boletín de la Asociación Provincial del Magisterio de primera enseñanza [The School: Bulletin of the Provincial Association of Primary Education] is one of the many professional pedagogical publications that appeared in Spain between the late 19th and early 20th centuries. Published in Castellón, it was mostly aimed at primary education teachers and it addressed a wide variety of education- related topics. In this work, we carry out a detailed analysis of the mathematics problem section that appeared in the bulletin from 1913 through 1916. Throughout the issues studied, we have identified four different periods in the section, featuring different approaches: problems to be implemented in the classroom or problems meant to engage the participation of the readers. Despite the restrictions involved in publishing graphics and figures in the bulletin, most of the problems are related to geometry, especially to the calculation of areas, volumes and lengths of different geometric figures, which for the most part require the use of algebraic techniques. Furthermore, the algebra used in many of the published solutions exceeds the contents that were studied at Normal Schools (Teacher Training Centers) of that time. The results of our study provide interesting information about the mathematical training of Spanish teachers in a specific historical and geographical context (Spanish provinces during the first quarter of the 20th century) and about the possible impact that this type of section could have had on the educational practice of readers